Expressions of URG4/URGCP, cyclin D1, Bcl-2, and Bax genes in retinoic acid treated SH-SY5Y human neuroblastoma cells - Dodurga, Yavuz; Gundogdu, Gulsah; Koc, Tugba; Yonguc, G. Nilufer; Kucukatay, Vural; Satiroglu-Tufan, N. Lale (Contemporary Oncology/Współczesna Onkologia, 2013)
Retinoic acid (RA) plays important roles in development, growth, and differentiation by regulating the expression of its target genes. The pro-apoptotic Bax gene may form channels through oligomerization in the mitochondrial membrane and facilitate the cytosolic release of cytochrome c. The anti-apoptotic Bcl-2 gene can inhibit this process. Up-regulated gene 4/Upregulator of cell proliferation ( URG4/URGCP ) is a novel gene located on 7p13. URG4/ URGCP also stimulates cyclin D1 ( CCND1 ) mRNA expression, and RNAi-mediated URG4/URGCP silencing diminishes CCND1 mRNA expression in HepG2 cells. In this study, the effects of RA treatment on URG4/URGCP , CCND1 , Bcl-2 and Bax gene expression changes in undifferentiated and differentiated SHSY5Y neuroblastoma cells was analyzed. SHSY5Y cells were cultured in the appropriate conditions. To induce differentiation, the cells were treated with 10 micromolar RA in the dark for 3-10 days. SHSY5Y cells possess small processes in an undifferentiated state, and after treatment with RA, the cells developed long neurites, resembling a neuronal phenotype. Total RNA was isolated with Tri-Reagent. Expression profiles of the target genes were determined by semi-quantitative RT-PCR. According to the results, Bcl-2 and CCND1 gene expression levels were increased, while URG4/URGCP and Bax gene expression was decreased in RA treated cells compared to the control cells. Our preliminary results suggest that RA may induce cell proliferation and escape apoptosis using a novel pathway by the URG4/URGCP gene. Further investigations are needed to clarify more direct transcriptional targets of RA signaling and the interaction of RA pathways with other pro-regenerative signals.